Book of Abstracts: FTA 2020 Science Conference - Forests, trees and agroforestry science for transformational change - Gitz, V.; Meybeck, A.; Ricci, F.; Belcher, B.; Brady, M.A.; Coccia, Federica; Elias, M.; Jamnadass, Ramni H.; Kettle, Christopher J.; Larson, A.M.; Li, Y.; Louman, Bastian; et al. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The CGIAR Research Program on Forests, Trees and Agroforestry (FTA) organized over 10 days from 14 to 25 September 2020 its decadal conference. The fully digital event titled Forest, trees and agroforestry science for transformational change gathered more than 500 scientists from the programme and its working partners, from 69 countries across the globe, with more than 100 presentations and 40 posters. The conference also featured a set of science – policy – implementation panel discussions, including around controversial issues, with high profile scientists and key stakeholders, as well as a series of keynote speeches.